Photo-enhanced O−, H− and Br− ion production in caesium sputter negative ion source—no evidence for resonant ion pair production. (3rd November 2022) - Hossain, A; Tarvainen, O; Reponen, M; Kronholm, R; Julin, J; Kalvas, T; Toivanen, V; Kivekäs, M; Laitinen, M
Abstract: It has been proposed that the negative ion yield of a caesium sputter ion source could be enhanced by promoting neutral caesium atoms to electronically excited 7p states supporting resonant ion pair production. We have tested this hypothesis by illuminating the cathode of a caesium sputter ion source with an adjustable wavelength laser and measuring its effect on the extracted beam currents of O −, H − and Br − anions. The laser exposure causes the beam currents to increase but the effect is independent of the wavelength in the range of 440–460 nm, which leads us to conclude that there is no evidence for resonant ion pair production. The photon-induced beam current enhancement scales with the applied laser power and, depending on the ion source conditions, can more than double the extracted beam current. We present a qualitative explanation for the observed effect. The model, based on photoelectron emission and subsequent increase of the caesium sputtering rate, thus liberating negative ions from the cathode, is supported by the data demonstrating that the caesium sputter ion source can produce Br − beams without thermal surface ionization as a source of Cs + ions, i.e. in external laser-driven mode without heating the surface ionizer.